Polylactide nanofibers with hydroxyapatite as growth substrates for osteoblast-like cells - Novotna, Katarina; Zajdlova, Martina; Suchy, Tomas; Hadraba, Daniel; Lopot, Frantisek; Zaloudkova, Margit; Douglas, Timothy E L; Munzarova, Marcela; Juklickova, Martina; Stranska, Denisa; Kubies, Dana; Schaubroeck, David; et al. (Journal of biomedical materials research. Part A, 2014)
Various types of nanofibers are increasingly used in tissue engineering, mainly for their ability to mimic the architecture of tissue at the nanoscale. We evaluated the adhesion, growth, viability, and differentiation of human osteoblast-like MG 63 cells on polylactide (PLA) nanofibers prepared by needle-less electrospinning and loaded with 5 or 15 wt % of hydroxyapatite (HA) nanoparticles. On day 7 after seeding, the cell number was the highest on samples with 15 wt % of HA. This result was confirmed by the XTT test, especially after dynamic cultivation, when the number of metabolically active cells on these samples was even higher than on control polystyrene. Staining with a live/dead kit showed that the viability of cells on all nanofibrous scaffolds was very high and comparable to that on control polystyrene dishes. An enzyme-linked immunosorbent assay revealed that the concentration of osteocalcin was also higher in cells on samples with 15 wt % of HA. There was no immune activation of cells (measured by production of TNF-alpha), associated with the incorporation of HA. Moreover, the addition of HA suppressed the creep behavior of the scaffolds in their dry state. Thus, nanofibrous PLA scaffolds have potential for bone tissue engineering, particularly those with 15 wt % of HA.
Keywords: buněčné linie; nanovlákna; osteoblasty; buněčná adheze; buněčná diferenciace; lidé; tkáňové inženýrství; osteokalcin; Bone Substitutes; Cell Adhesion; Nanofibers; Osteocalcin; Polyesters; Cell Line; Durapatite; Osteoblasts; kostní náhrady; Cell Differentiation; Tissue Engineering; Cell Survival; viabilita buněk; polyestery; hydroxyapatit; Humans